PENGARUH KUALITAS SMARTPHONE XIAOMI TERHADAP KEPUASAN PELANGGAN DI SITUASI PANDEMI COVID-19 - Rasyid, Mohammad Kurniadi (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
This study aims to determine the effect of product quality on customer satisfaction of Xiaomi handphones in Covid-19’s era. The approach used in this study is a quantitative approach with data analysis techniques using Partial Least Square Structural Equation Modeling (PLS-SEM). The questionnaire was distributed to 55 Xiaomi mobile phone users in the Jabotabek area. The results show that the quality of Xiaomi mobile phones has a significant effect on customer satisfaction. Customer assessment of the level of satisfaction is in the high category with a percentage of 60%, this shows that customers are satisfied with Xiaomi products. Customer assessment for the level of product quality, including the medium category with a percentage of 54.6%.